Human Rights Reflected in Flowers for Algernon (1966) Novel by Daniel Keyes: A Sociological Approach - Yuliawan, Dwi Nanda; , Titis Setyabudi, S.S. M. Hum (2017)
This study aims to find out the human rights and analyze the purpose of Daniel Keyes toward Flowers for Algernon (1966) novel. The writer uses qualitative method. The writer uses two data sources: primary and secondary. Primary data source is Flowers for Algernon (1966) novel by Daniel Keyes. Secondary data source includes literature books, articles, and website that are related to the novel and the author. Method of collecting data is descriptive. Technique of analyzing data uses descriptive qualitative. Based on the sociological analysis, the writer finds five aspects, including: social aspect, economic aspect, scientific and technological aspect, cultural aspect, and religion aspect in the Flowers for Algernon (1966) novel by Daniel Keyes. Daniel Keyes states that all of human beings have equal rights, parents must realize their potential child, and as the member of society, we must change our mindset toward disabilities. Keywords: human rights, the author's purpose, sociological approach